2022
DOI: 10.1109/tvcg.2021.3114770
|View full text |Cite
|
Sign up to set email alerts
|

Accessible Visualization via Natural Language Descriptions: A Four-Level Model of Semantic Content

Abstract: Fig. 1. Visualizations like "Flatten the Curve" (A) efficiently communicate critical public health information, while simultaneously excluding people with disabilities [11, 28]. To promote accessible visualization via natural language descriptions (B, C), we introduce a four-level model of semantic content. Our model categorizes and color codes sentences according to the semantic content they convey.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
74
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(105 citation statements)
references
References 80 publications
0
74
0
Order By: Relevance
“…However, each of these three approaches comes with its own limitations. Static alt text requires blind readers to accept the author's interpretation of the data; by not affording exploratory and interactive modes, alt text robs readers of the necessary time and space to interpret the numbers for themselves [LS21]. Recent research also suggests that blind people have nuanced preferences for the kinds of visual semantic content conveyed via text [PGFM21; LS21], and desire more interactive and exploratory representations of pictorial images [MJBC18].…”
Section: Background and Related Workmentioning
confidence: 99%
“…However, each of these three approaches comes with its own limitations. Static alt text requires blind readers to accept the author's interpretation of the data; by not affording exploratory and interactive modes, alt text robs readers of the necessary time and space to interpret the numbers for themselves [LS21]. Recent research also suggests that blind people have nuanced preferences for the kinds of visual semantic content conveyed via text [PGFM21; LS21], and desire more interactive and exploratory representations of pictorial images [MJBC18].…”
Section: Background and Related Workmentioning
confidence: 99%
“…Most related to our work is a recent paper by Lundgard & Satyanarayan that began to formalize the semantic content of textual descriptions of charts [35]. They developed a conceptual model that spans four levels of semantic content: enumerating visualization construction properties (e.g., marks and encodings); reporting statistical concepts and relations (e.g., extrema and correlations); identifying perceptual and cognitive phenomena (e.g., complex trends and patterns); and elucidating domain-specific insights (e.g., social and political context).…”
Section: Accessibility (Blind and Low Vision)mentioning
confidence: 99%
“…In this study, we utilize the framework from Lundgard & Satyanarayan [35] which describes four semantic levels:…”
Section: Studymentioning
confidence: 99%
See 1 more Smart Citation
“…However, such alternative texts and captions are often not much helpful or not available at all [MJBC18]. A recent study found that chart description should explain important trends and key statistics rather than simply saying how the data is encoded [LS22]. In this context, introducing chart question answering could significantly advance the field of accessible data visualizations [SWM * 22].…”
Section: Challenges and Research Opportunitiesmentioning
confidence: 99%